The reality of applying transformational leadership in the school administration of the secondary school pathways system in Riyadh - Al-Otaibi, Ameera Ayedh; Al-Juhani, Areej Makki (Journal of Educational and Psychological Sciences, 2023)
This study aimed to identify the reality of the application of transformational leadership in the school administration of the secondary school pathways system in the Riyadh. It was distributed to a random sample of the study population, which amounted to (200) principals and undersecretaries in secondary schools in the city of Riyadh. ,19), with a relative weight of (84%). The level of appreciation of the study sample for each of the dimensions of "inspirational motivation" and "ideal influence" as one of the dimensions of transformational leadership was very high, as the general average of the attitudes of the sample was (4.23), with a relative weight of (85%) for each dimension. It also became clear that the level of appreciation of the study sample for each of the dimensions of "intellectual stimulation" and "individual considerations" as one of the dimensions of transformational leadership came to a high degree, as the general average of the attitudes of the sample was (4.15), with a relative weight of (83%) for each dimension. The level of the sample’s assessment of the obstacles to implementing transformational leadership in the Pathways system came to a medium degree, with a general average of (3.78), with a relative weight of 76%. The Pathways system focuses on developing transformative leadership skills and enhancing awareness of their importance and benefits, promoting a culture of change and innovation in secondary schools by holding awareness and training sessions for teachers and administrators, also enhancing communication and cooperation between secondary school leaders by establishing opportunities for professional exchange and joint workshops to discuss challenges and successful practices in Implementing transformational leadership in the paths system, improving the appointment policy and evaluating administrative leaders.